Effects of a physical activity intervention on schoolchildren's health-related quality of life: The active smarter kids (ASK) cluster-randomized controlled trial - Resaland, Geir Kåre (Prev Med Rep, 2018)
We investigated whether a seven-month (November 2014 to June 2015), school-based cluster-randomized controlled physical activity intervention improved health-related quality of life (HRQoL) in 10-year old children. The participants (N = 1229) from 57 elementary schools in Sogn og Fjordane County, Norway, were cluster-randomized by school either to the intervention (I) or control (C) group. The planned intervention in the 28 I-schools was 300 min of physical activity per week, compared to 135 min in the 29C-schools. HRQoL was assessed by self-report, using the Kidscreen-27 questionnaire. Objectively measured physical activity did not differ between the I–schools and C-schools during the intervention. No effect of the intervention was found for HRQoL: Physical well-being (P = 0.789), Psychological well-being (P = 0.682), Autonomy & parents (P = 0.662), Social support & peers (P = 0.828) and School environment (P = 0.074). In conclusion, the ASK school-based physical activity intervention showed no significant effect on HRQoL.